Pembuatan Aplikasi Persediaan Barang Berbasis Web Pada PT. Bayan Resources Tbk - Ririn Wahyuni; Muhammad Taufiq Sumadi; Naufal Azmi Verdikha (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to design and implement a web-based Goods Inventory Information System at PT Bayan Resources Tbk. The company faces challenges in inventory management, such as stock uncertainty, variations in order cycle time, and operational efficiency levels that need to be improved. Waterfall method is used as a framework for system development, with stages of requirement analysis, design, implementation, testing, and maintenance. The system is designed to improve operational efficiency through integration of inventory data, order management, and item tracking. The result is a web-based application with features such as a secure login page, informative dashboard, master data management, efficient input of incoming and outgoing goods, and careful user control. With the implementation of dark mode, the system gives users the flexibility to customize the display according to their preferences. Users can easily access, track, and analyze inventory data, supporting faster and more accurate decision-making for the company.